Successful recording perioperarive hemodynamic changes with the severe right diaphragmatic hernia - Noboru Inamura; Tomohiko Tanaka; Akio Kubota; Yuko Tazuke; Akihiro Yoneda; Hisayuki Kawahara; Futoshi Kayatani (Elsevier, 2016)
We experienced a case of severe congenital diaphragmatic hernia (CDH) with severe deleterious hypoxemia after birth in which we succeeded in saving the patient with radical surgery. Observation of the patient's detailed hemodynamics was possible for the entire perioperative period. The central venous pressure (CVP) was high according to the pressure in the liver. The CVP subsequently decreased after the operation, and the oxygen saturation increased. Therefore, the cardiac diastolic disorder improved. This case suggests that the diastolic dysfunction in severe CDH patients is worsen by compression from herniated visceral organs.